Jeong Hagok on Emotions and the Korean Four-Seven Debate: A Confucian, Comparative, and Contemporary Interpretation - Chung, Edward Y. J. (Religions, 2023)
This article presents Jeong Jedu (Hagok; 1649–1736) on the topic of emotions and its comparative and contemporary relevance. It discusses this leading neo-Confucian thinker’s thought-provoking Four-Seven thesis and its vital implication for self-cultivation and ethics. This important topic has not been discussed in current scholarship on Korean Confucianism. The article begins with the Confucian notion of emotions (jeong/qing, 情), according to its textual and philosophical background in the Chinese tradition, and then covers key issues regarding the “Four Beginnings” of virtue, the “Seven Emotions”, and leading neo-Confucian perspectives by Zhu Xi (1130–1200) and Wang Yangming (1472–1529). The article also provides a brief comparative analysis of Toegye’s and Yulgok’s leading Korean opinions on the nature, role, and problem of emotions. The third section focuses on Hagok’s interpretation in the same context. The fourth section discusses Hagok’s ethics and spirituality of emotions in terms of the mind’s original essence (bonche/benti) and innate knowledge (of good) (yangji/liangzhi) in connection to Wang Yangming’s doctrines. The final section concludes by considering the originality and distinctiveness of Hagok’s holistic interpretation. It also presents my contemporary reflections to articulate how Hagok’s groundbreaking insights compare with certain Western theories of emotions and why they offer a worthwhile resource for comparative philosophy, religion, and ethics.